Between shaming corporations and promoting alternatives: The politics of an "ethical shopping map". (July 2014) - Balsiger, Philip
Ethical consumption can take different forms, some more contentious like boycotts or public campaigns, some aiming at the establishment or promotion of alternative consumption practices (buycotts). This study looks at how these tactics are articulated by analyzing the development of an "ethical shopping map, " an action situated in the latter category of "supportive" actions. In 2007, a Swiss nongovernmental organization published this map as part of its ongoing campaign fighting for the respect of social standards in the global garment industry. A project pursued by a regional group of volunteers of the organization, the map listed stores where ethical clothes can be purchased in a big Swiss city. This article consists of an ethnographic analysis of the process of elaboration of the map and discusses its inclusion into the tactical repertoire of the anti-sweatshop campaign. Based on participant observation and interviews with volunteers and campaign staff, it examines what drives the activists' concern with alternative forms of consumption. It looks at the rationales and meanings the volunteers put behind the map and the different uses of the map that are suggested, and examines the ultimate "failure" of making it a lasting part of the campaign's tactical action repertoire. Doing so, the article reveals the inherent tension of "ethical consumption, " between supportive action forms based on buycotts and denunciatory actions of public shaming of firms whose practices are criticized.